The originals. Season 5 : the final season. - Morgan, Joseph, 1981-; Gillies, Daniel, 1976-; Tonkin, Phoebe, 1989-; Davis, Charles Michael, 1984-; Gateqood, Yusuf, 1982-; Voelkel, Riley, 1990- (Burbank, CA : Warner Bros. Home Entertainment, 2018)
The final season begins seven years after the core members of the Mikaelson family, Klaus, Elijah, Rebekah and Kol, each absorb a quarter of the Hollow2s dark energy and flee New Orleans to keep their beloved city and young Hope safe. As the Mickaelsons return to New Orleans, bringing the pieces of a century2s old evil with them, it becomes clear that the closing chapter of this family saga will be as bloody and emotional as ever.
Disc 1. Where you left your heart ; One wrong turn on Bourbon ; Ne me quitte pas ; Between the devil and the deep blue sea ; Don't it just break your heart -- disc 2. What, will, I, have, left ; God's gonna trouble the water ; The kindness of strangers ; We have not long to love -- disc 3. There in the disappearing light ; 'Til the day I die ; The tale of two wolves ; When the saints go marching in.
Title from disc container.
Originally aired on television in 2017.
Widescreen.
Joseph Morgan, Daniel Gillies, Phoebe Tonkin, Charles Michael Davis, Leah Pipes, Danielle Campbell, Riley Voelkel, Yusuf Gatewood..
Not rated; q CHV rating: 14A.
DVD, region 1; Dolby Digital 5.1 surround.
Keywords: Television serials; Horror television programs; Fantasy television programs; Vampire television programs; Werewolf television programs; Adventure television programs